Pengembangan Bahan Ajar Tematik Pendamping Guru dengan Model Webbed - Hastanto, Andreas Bagus; Atiqoh, Atiqoh; Karyono, Hari (LP. Ma'arif Janggan Magetan, 2023)
The objectives of the research are: (1) To produce teaching materials in the form of Teacher's Companion Thematic Books for class II elementary school students, and (2) To determine the suitability of teaching materials in the form of Teacher's Companion Thematic Books for class II elementary school students. This development study follows the development stages of the ADDIE model. This research produced: (1) Teaching Material Books which were developed using Microsoft Word 2019 software, the final results of which are physical books and PDF files that can be accessed by devices with applications that can open these types of files. (2) The design expert's assessment shows that the teaching material book is classified as very feasible with an assessment percentage of 91.76%, from communication experts it is classified as very feasible with a percentage of 87.14%, from material experts it is classified as very feasible with a percentage of 93.68%, from users namely colleagues obtained an evaluation percentage of 90.87% which was classified as very worthy, from the answers of students in small groups, namely 9 students, achieved an evaluation percentage of 85.19% which was classified as worthy, and the large group, namely 38 students, achieved very decent results with percentage 90.18%.